Taxonomic studies on Leucospis Fabricius collection (Hymenoptera: Chalcidoidea: Leucospidae) at Annamalai University, Tamil Nadu, India. (2nd January 2020) - Sankararaman, Hariharakrishnan; Manickavasagam, Sagadai; Ghorpade, Kumar D.
ABSTRACT: Taxonomic studies on leucospid specimens (Chalcidoidea: Leucospidae) in the department of Entomology, Annamalai University is furnished which includes five out of seven spec-ies of the genus Leucospis Fabricius known from India, viz., L. guzeratensis Westwood, L. histrio Maindron, L. pediculata Guérin-Méneville, L. petiolata Fabricius and L. pyriformis (Weld). Leucospis pediculata is reported from Kerala and L. petiolata from Maharashtra and Meghalaya. Information on the parasitoid distribution, brief diagnosis of each species with high-resolution images of habitus and other essential parts for easy identification are provided. An identification key to Indian species of Leucospis is also included. http://www.zoobank.org/urn:lsid:zoobank.org:pub:7B774E86-F8BA-42B7-86E2-0033146D5FC0